2008
DOI: 10.1590/s1516-44462008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Structural magnetic ressonance imaging in anxiety disorders: an update of research findings

Abstract: Objective: The aim of the present report is to present a systematic and critical review of the more recent literature data about structural abnormalities detected by magnetic ressonance in anxiety disorders. Method: A review of the literature in the last five years was conducted by a search of the Medline, Lilacs and SciELO indexing services using the following key words : "anxiety", "panic", "agoraphobia", "social anxiety", "posttraumatic" and "obsessive-compulsive", crossed one by one with "magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 89 publications
(173 reference statements)
3
35
0
3
Order By: Relevance
“…There is strong evidence that the vulnerability to panic disorder is partly genetic, with heritability estimated to be about 48% (Hettema et al 2001). In addition to the gray matter reduction in medial prefrontal regions seen across anxiety disorders, replicated brain morphometric findings in panic disorder include reduced volume of lateral and medial temporal lobe regions (Ferrari et al 2008) and increased gray matter volume of the midbrain and pons (Protopopescu et al 2006;Uchida et al 2008). We could find no published studies of postmortem brain tissue from patients with panic disorder.…”
Section: Panic Disordermentioning
confidence: 99%
“…There is strong evidence that the vulnerability to panic disorder is partly genetic, with heritability estimated to be about 48% (Hettema et al 2001). In addition to the gray matter reduction in medial prefrontal regions seen across anxiety disorders, replicated brain morphometric findings in panic disorder include reduced volume of lateral and medial temporal lobe regions (Ferrari et al 2008) and increased gray matter volume of the midbrain and pons (Protopopescu et al 2006;Uchida et al 2008). We could find no published studies of postmortem brain tissue from patients with panic disorder.…”
Section: Panic Disordermentioning
confidence: 99%
“…17; 18 As a result of aberrant communication between these cortical and subcortical regions, the system interprets and responds as if danger were present, and this over response in the system has been implicated in anxiogenesis. 18 Notably, the brain regions implicated in the fear response system have not been examined in children with epilepsy with anxiety disorders. The second aim of this study is to examine the critical neuroanatomical regions reviewed above in this distributed fear system in children with recent-onset epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the genetics, physiology and neurochemistry of GAD have shown that the amygdala, the prefrontal cortex and the temporal areas are among the brain structures identified to participate in the responses to emotional processing and social behaviors [56], and therefore may count on abnormal GABAergic transmission. However, these regions appear to abnormally function on other anxiety disorders [57], a feature that limits the specificity of the findings.…”
Section: The Neurobiology Of Anxiety: Involvement Of the Gabaergic Symentioning
confidence: 94%